SAT0121 PAIN AND OTHER PATIENT-REPORTED OUTCOMES IN PATIENTS WITH RHEUMATOID ARTHRITIS WHO DID OR DID NOT ACHIEVE TREATMENT RESPONSE BASED ON IMPROVEMENT IN SWOLLEN JOINTS IN TOCILIZUMAB CLINICAL TRIALS. (2nd June 2020) - Sebba, A.; Han, J.; Mohan, S.
Abstract : Background: Significant improvements in pain and other patient-reported outcomes (PROs) have been shown in large clinical trials in patients with rheumatoid arthritis (RA) who receive tocilizumab (TCZ) compared with placebo (PBO). Recent data suggest that pain in RA may be noninflammatory as well as inflammatory, and improvement in pain scores and other PROs may be seen in patients who do not respond to treatment based on disease activity measures that evaluate inflammation. Objectives: To assess changes in pain scores and other PROs in patients with RA who did or did not achieve ≥ 20% improvement in SJC in TCZ clinical trials. Methods: Data from patients with active RA who received intravenous TCZ 8 mg/kg + MTX or PBO + MTX in 3 Phase III studies (OPTION [NCT00106548 ], TOWARD [NCT00106574 ] and LITHE [NCT00109408 ]) were included. All patients had moderate to severe RA with an inadequate response or intolerance of MTX (OPTION, LITHE) or conventional synthetic disease-modifying antirheumatic drugs (csDMARDs; TOWARD). Changes in pain (visual analog scale [VAS], 0-100 mm), Health Assessment Questionnaire Disability Index (HAQ-DI, 0-3), 36-Item Short Form Survey (SF-36) physical component score (PCS) and mental component score (MCS; 0-50) and Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue score (0-52) from baseline to Week 24 were evaluated. Results were compared between patients receiving TCZ + MTX and those receiving PBO + MTX in both patients who achieved ≥ 20% improvement in SJC (responders) and those who did not (nonresponders). The changes from baseline were analyzed using a mixed model with repeated measures, including the following covariates and interactions: treatment, visit, baseline of endpoint, region, baseline DAS28 and interactions of visit with treatment and baseline of endpoint. Results: Data from 1254 responders (TCZ + MTX, n = 831; PBO + MTX, n = 423) and 620 nonresponders (TCZ + MTX, n = 225; PBO + MTX, n = 395) were included. Patients receiving TCZ + MTX had significantly greater improvement in pain scores and HAQ-DI compared with PBO + MTX in the responder group (–27.19 vs –16.77 and –0.55 vs –0.34, respectively; P < 0.0001 for both) and nonresponder group (–9.59 vs 2.53 and –0.20 vs 0.01; P < 0.0001 for both) at Week 24 (Figure 1 ). Similar results were seen at Week 16 in the nonresponder group (–11.06 vs –2.38 and –0.23 vs –0.04; P < 0.0001 for both) prior to initiation of rescue treatment. At Week 24 in the responder group, patients receiving TCZ + MTX had significantly greater improvements compared with PBO + MTX in SF-36 PCS and MCS (9.16 vs 5.71 and 6.55 vs 3.79, respectively; P < 0.0001 for both) (Figure 2 ) and FACIT-Fatigue (8.39 vs 5.11; P < 0.0001). In the nonresponder group, patients receiving TCZ + MTX had significantly greater improvements compared with PBO + MTX in SF-36 PCS at Week 16 (3.81 vs 1.65; P = 0.0006) and Week 24 (4.42 vs 1.01; P < 0.0001) (Figure 2 ) and FACIT-Fatigue at Week 16 (3.82 vs 1.32; P = 0.0039) and Week 24 (3.90 vs 1.40; P = 0.0111). Conclusion: Patients with RA who received TCZ + MTX had significantly greater improvements in pain score and other PROs than those who received PBO + MTX regardless of whether they achieved ≥ 20% improvement in SJC. Clinical outcome at Week 24 correlated well with PROs, with a relatively larger improvement in pain score and other PROs in the responder group than in the nonresponder group; relative to PBO + MTX, these improvements appear numerically similar in the responder and nonresponder groups with consistently smaller difference between the groups in TCZ-treated arms. The consistent effect of TCZ on PROs in both responder and nonresponder groups warrants further study on the impact of TCZ on sources of pain independent of that caused by joint inflammation. Figure: Acknowledgments: This study was sponsored by Genentech, Inc. Support for third-party writing assistance, furnished by Health Interactions, Inc, was provided by Genentech, Inc. Disclosure of Interests: Anthony Sebba Consultant of: Genentech, Gilead, Lilly, Regeneron Pharmaceuticals Inc., Sanofi, Speakers bureau: Lilly, Roche, Sanofi, Jian Han Shareholder of: Genentech, Inc., Employee of: Genentech, Inc., Shalini Mohan Shareholder of: Genentech, Inc., Employee of: Genentech, Inc.